Becoming a first-time father during the COVID-19 pandemic in France - Jean-Dit-Pannel, Romuald; Belot, Rose-Angélique; Mellier, Denis; Robert, Laura; Petersen, Célia; Dinet, Benoît; Bréhat, Cécile; Koliouli, Flora (Frontiers in Psychiatry, 2024)
The role of fathers in Western societies has undergone significant change over time. However, their psychopathology remains largely misunderstood and difficult to identify. This study aims to explore the lived experiences of first-time fathers during the COVID-19 pandemic. Twenty-seven first-time French fathers were recruited for the study, which involved a narrative interview, the Rorschach projective test, the Edinburgh Postnatal Depression Scale (EPDS), and a semi-structured interview. Narrative interviews revealed several challenges faced by these fathers, including the pressure of paternal responsibility, the